In Situ Production of Exopolysaccharides during Sourdough Fermentation by Cereal and Intestinal Isolates of Lactic Acid Bacteria - Tieking, Markus (American Society for Microbiology, 2003)
EPS formed by lactobacilli in situ during sourdough fermentation may replace hydrocolloids currently used as texturizing, antistaling, or prebiotic additives in bread production. In this study, a screening of >100 strains of cereal-associated and intestinal lactic acid bacteria was performed for the production of exopolysaccharides (EPS) from sucrose. Fifteen strains produced fructan, and four strains produced glucan. It was remarkable that formation of glucan and fructan was most frequently found in intestinal isolates and strains of the species Lactobacillus reuteri, Lactobacillus pontis, and Lactobacillus frumenti from type II sourdoughs. By the use of PCR primers derived from conserved amino acid sequences of bacterial levansucrase genes, it was shown that 6 of the 15 fructan-producing lactobacilli and none of 20 glucan producers or EPS-negative strains carried a levansucrase gene. In sourdough fermentations, it was determined whether those strains producing EPS in MRS medium modified as described by Stolz et al. (37) and containing 100 g of sucrose liter(−1) as the sole source of carbon also produce the same EPS from sucrose during sourdough fermentation in the presence of 12% sucrose. For all six EPS-producing strains evaluated in sourdough fermentations, in situ production of EPS at levels ranging from 0.5 to 2 g/kg of flour was demonstrated. Production of EPS from sucrose is a metabolic activity that is widespread among sourdough lactic acid bacteria. Thus, the use of these organisms in bread production may allow the replacement of additives.